GREEN BANKING, ENVIRONMENTAL RESPONSIBILITY, AND SUSTAINABLE PERFORMANCE OF ISLAMIC BANKS: THE MEDIATING ROLE OF ENVIRONMENTAL INNOVATION - Riko Kurniawan; Refky Fielnanda (UIN Sulthan Thaha Saifuddin Jambi, 2026)
This study aims to examine the effects of green banking practices and environmental responsibility on the sustainable performance of Islamic banks, as well as to investigate the mediating role of environmental innovation in these relationships. The study is motivated by the growing global demand for sustainable financial practices, while empirical evidence explaining how environmental innovation enhances the sustainability performance of Islamic banking remains limited, particularly in regional contexts. A quantitative approach was employed using Structural Equation Modeling (SEM). The sampling procedure applied cluster random sampling. Of the three Islamic bank branches operating in Jambi City, two branches were randomly selected as research clusters. Survey data were collected from customers of the selected branches, resulting in 300 valid respondents, which meets the recommended sample size for SEM analysis. The study examines four key constructs: green banking, environmental responsibility, environmental innovation, and sustainable performance of Islamic banks. The findings reveal that green banking practices and environmental responsibility have a positive and significant effect on the sustainable performance of Islamic banks. Furthermore, environmental innovation plays a significant mediating role, strengthening the impact of green banking and environmental responsibility on sustainable performance. These results indicate that sustainable performance in Islamic banking is not only driven by environmental commitment but also by the bank’s ability to continuously develop and implement environmental innovations.